Christian-Muslim dialogue : perspectives of four Lebanese thinkers - Hirvonen, Heidi. (The History of Christian-Muslim Relations, 2013)
Lebanon is a significant region of encounter between Muslims and Christians in the Middle East. This book examines how Christian-Muslim dialogue is envisioned by four present-day Lebanese thinkers: Great Ayatollah Muhammad Husayn Fadlallah and Doctor Mahmoud Ayoub from the Shiite tradition, and Metropolitan Georges Khodr and Doctor, Father Mouchir Basile Aoun from the Eastern Christian Antiochian tradition. The study seeks to bring the four thinkers into dialogue on a number of topics, including doctrinal themes, ethical principles and the issue of political power-sharing in Lebanon. All four thinkers make several suggestions for facilitating mutual understanding and transcending old debates. The concept of God and the principle of neighbourly love seem to have particular potential as fruitful bases for further dialogue.